Mirza Ghulam Ahmad Qadiani's Concept of Imam Mahdi (A.S.) : A Research-Based, Critical, and Scholarly Analysis": DOI: https://doi.org/10.5281/zenodo.15163278 (Khairulummah, 2024)
Mirza Ghulam Ahmad Qadiani, among his numerous assertions, also made the significant claim of being the "Mahdi," although his primary assertion was prophethood. However, Qadianis refrain from openly acknowledging Mirza's prophethood in the presence of general Muslims and instead attempt to create the impression that their disagreement is solely over the issue of Imam Mahdi. They recognize Mirza as Imam Mahdi. Mirza himself made various claims to Mahdi-hood, as he stated:(a) "Indeed, I am the Promised Messiah and the Promised Mahdi."(b) "I swear by the God who sent me and upon whom attributing falsehood is the act of the accursed, that He has sent me as the Promised Messiah."Even if the Qadianis' claim is accepted, facts and events reveal that Mirza Ghulam Ahmad Qadiani's personality and character are inconsistent with the expected attributes. This is because none of the signs and descriptions of Imam Mahdi mentioned in the sayings of the Prophet Muhammad (peace be upon him) align with the person of Mirza. In this article, first of all, the signs of the Mahdi mentioned in the hadiths - without entering into discussions on the authenticity of these hadiths - are compared with the claims of Mirza Ghulam Ahmad. Then, based on this comparison, an evaluation is made regarding Mirza Ghulam Ahmad's claim to be the Mahdi. In our article, we will not go into a theoretical discussion on the subject of Mahdi, such as the idea of ​​a savior in world religions, the possibility of the coming of the Mahdi, the lifespan of the Mahdi and its possibility, etc.